2009
DOI: 10.1080/07380570902773305
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Evidence-Based Practice by Occupational Therapists

Abstract: The purpose of this study was to explore occupational therapists' attitudes, knowledge, and use of evidence-based practice. Results indicated that therapists have positive attitudes toward evidence-based practice; however, use of research evidence in practice remains limited primarily due to lack of time. Suggestions for clinical and academic partnerships are offered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
69
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 12 publications
7
69
0
1
Order By: Relevance
“…While the EBP process has been clearly delineated and OT clinicians are frequently reminded of the importance of basing their clinical decisions on scientific evidence, several studies have found that OTs are not incorporating research findings in their practice [4][5][6][7]. Researchers in the USA [4,7] surveyed OTs to examine the use of evidence in practice and found that although the majority of therapists had favourable attitudes towards EBP and felt that EBP should be an essential part of clinical practice, only 38% of surveyed clinicians reported using research findings in their practice [7].…”
Section: Gaps Between Actual Practice and Ebpmentioning
confidence: 99%
See 2 more Smart Citations
“…While the EBP process has been clearly delineated and OT clinicians are frequently reminded of the importance of basing their clinical decisions on scientific evidence, several studies have found that OTs are not incorporating research findings in their practice [4][5][6][7]. Researchers in the USA [4,7] surveyed OTs to examine the use of evidence in practice and found that although the majority of therapists had favourable attitudes towards EBP and felt that EBP should be an essential part of clinical practice, only 38% of surveyed clinicians reported using research findings in their practice [7].…”
Section: Gaps Between Actual Practice and Ebpmentioning
confidence: 99%
“…There is good evidence that findings from scientific research are not routinely used to inform decisions about patient care [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The perception of EBP is increasingly positive (Thomas & Law, 2013); however, research used among occupational therapists continues to be low (Salls, Dolhi, Silverman, & Hansen, 2009;Thomas & Law, 2013). Previous research suggests only 12% of practicing occupational therapists in Pennsylvania engage in EBP (Salls et al, 2009), yet in the present study, 72.5% (n = 29) of the survey respondents and 33% (n = 2) of the interview participants report regularly incorporating EBP assignments into the fieldwork experience.…”
Section: Suggestions On How Fieldwork Can Be Improvedmentioning
confidence: 60%
“…The perception of EBP is increasingly positive (Thomas & Law, 2013); however, research used among occupational therapists continues to be low (Salls, Dolhi, Silverman, & Hansen, 2009;Thomas & Law, 2013). Previous research suggests only 12% of practicing occupational therapists in Pennsylvania engage in EBP (Salls et al, 2009), yet in the present study, 72.5% (n = 29) of the survey respondents and 33% (n = 2) of the interview participants report regularly incorporating EBP assignments into the fieldwork experience. Although some evidence suggests that supervising students is associated with an increased use of evidence in practice (Craik & Rappolt, 2006), the popularity of EBP assignments may be better understood as a response to increased pressure from academic fieldwork coordinators to assess students' research and appraisal skills.…”
Section: Suggestions On How Fieldwork Can Be Improvedmentioning
confidence: 60%